Classical and Recent Methods of Enterprise Diagnostics - Ondrej Buček; Milada Bučková (Communications - Scientific letters of the University of Zilina, 1999)
This article deals with both classical and more recent methods of diagnostics which may be used when making diagnostics of enterprise. Besides the basic terms there is defined also the relation of the diagnostics toward the analysis, controlling and finally to the information systems. The application of methods and techniques of diagnostics is analysed in relation to the evaluation of both external as well as internal factors.